Recreational travel cost to Larut Matang, Mangrove Forest - Zainol, Rodziah (2016)
Outdoor recreational experience is one of the services provided in many natural areas. In planning for the development and operation of outdoor recreational opportunities in public land, valuation of the area is mostly done by establishing a recreational demand model curve. This study is conducted in the state of Perak. This study aims to determine the recreational, economic value using the travel cost method in Matang, Mangrove Forest. The data obtained with a sample size of 300 is modeled using a linear regression model. Based on this study, five variables that were tested, which are travel cost, job, income, gender and conservation of forests. The variables that showed a significant value at a confidence level of 0.05 which explain the demand for LMMF were travelling cost, gender and conservation. An estimate of consumer surplus (CS) per trip per user, as well as the total recreational value of 2015, was computed. The total estimation recreational, economic value in LMMF 2015 was calculated as a total of RM6651.3 year. This data is vital for the stakeholders, especially Perak Forestry Department to value this area as one of the crucial and valuable natural resources that have the potential to be developed into an economic growth area that could benefit to improve the livelihood of the local community.